Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.12816/0041516
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice about Allergic Rhinitis in Saudi Arabia, 2017

Abstract: Background: allergic rhinitis (AR) is considered a worldwide health disease therefore the lack of knowledge would result in poor adherence to management and preventive protocols and increasing the prevalence of AR. Objectives: evaluating the knowledge, attitude and practice(KAP) of Saudi adult subjects toward AR in Kingdom of Saudi Arabia (KSA). Methods: a cross sectional study conducted on 900 Saudi adult subjects admitted to primary health care centers. The subjects were interviewed and filled up a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 4 publications
3
28
2
Order By: Relevance
“…Muhamad et al found limited knowledge and practice among the female patients in primary care facilities in Malaysia ( 32 ), while Fahs et al found good knowledge of CVD risk factors among the Lebanese population ( 23 ). Concerning stroke risk factors and warning symptoms, a study of Saudis by Alreshidi et al found that 63.8% of their participants had insufficient knowledge, attitudes, and practice ( 33 ). A second study by Alhazzani also showed a deficit in knowledge about strokes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Muhamad et al found limited knowledge and practice among the female patients in primary care facilities in Malaysia ( 32 ), while Fahs et al found good knowledge of CVD risk factors among the Lebanese population ( 23 ). Concerning stroke risk factors and warning symptoms, a study of Saudis by Alreshidi et al found that 63.8% of their participants had insufficient knowledge, attitudes, and practice ( 33 ). A second study by Alhazzani also showed a deficit in knowledge about strokes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire explored 11 domains: (1) screening (International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire), 15 (2) family medical history, (3) parent-perceived burden (as assessed by the validated single health status question; 16 and the validated Healthy Days questionnaire 17 and impact of AR on day-to-day living (adapted from Pediatric Allergies in America Survey)), 18 (4) beliefs about medicines (Beliefs about Medicines questionnaire), 19 (5) knowledge and beliefs about allergies (knowledge, attitude and practice questions in AR and asthma), 20–22 (6) AR classification (ARIA criteria), 1 23 (7) AR diagnosis, (8) AR triggers and testing, (9) AR symptoms (Contre les MAladies Chroniques pour un VIeillissement Actif (MACVIA)-ARIA validated visual analogue scales (VAS) 3 24 25 ), (10) symptom control (Control of Allergic Rhinitis and Asthma Test for Children) 26 and (11) AR management strategies. The length of the questionnaire was a key consideration; to minimise bias resulting from questionnaire fatigue, data collected about the survey respondents (parents/guardians) were minimal, with the majority of data relating to the specified child on whose behalf the questionnaire was being completed.…”
Section: Methodsmentioning
confidence: 99%
“…AR is a non-contagious inflammatory disease; it is caused by nasal hypersensitivity where immunoglobulin E is induced after a single allergen encounter, which results in an allergic reaction triggering inflammation 1 1 1 2 1 [6,10]. The inflammatory process caused by AR is similar to that found in other atopic inflammatory disorders, such as asthma, allergic conjunctivitis, and rhinosinusitis; a high asthma prevalence has been found in patients with severe cases of AR [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Allergic rhinitis (AR) is considered to be a common chronic respiratory disease in the general population, and it is one of the most common chronic diseases of childhood, representing a major public health concern in many countries worldwide [2][3][4][5]. In terms of prevalence, AR is estimated to affect from 10% to 35% of the population; however, these percentages could be inaccurate because some patients do not consider AR to be a disease [6,7]. In Saudi Arabia, a study conducted on 807 residents of the city of Al-Ahsa revealed that 76% of the study sample had been diagnosed with AR and had symptoms suggestive of AR [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation